IMPACT OF STRUCTURED PEER-ASSISTED LEARNING ON ANATOMY TOPICS: A JIGSAW METHOD APPROACH - SIRIKONDA, PARIMALA; ZISHAAN, MOHD IMTESAL ALI; MARIYA; SIRIKONDA, NIVEDITHA (International Journal of Current Pharmaceutical Research, 2026)
Objective: To evaluate the effectiveness of structured peer-assisted learning using the Jigsaw method in improving understanding, retention, teamwork, communication skills, and overall academic performance among Phase-I MBBS students in anatomy. Methods: A pre-test and post-test interventional study was conducted among 150 Phase-I MBBS students in the Department of Anatomy, Government Medical College, Mahabubnagar. Students participated in a structured Jigsaw learning session covering selected anatomy topics. A 15-item multiple-choice questionnaire was administered before and after the intervention. Scores were analyzed using paired statistical methods. Results: The mean pre-test score was 7.0±2.1, which improved significantly to 14.0±1.3 in the post-test. The improvement was statistically significant (p<0.0001) with a very large effect size (Cohen’s d = 1.85). There was a marked reduction in low scorers and a substantial increase in high achievers. Conclusion: Structured peer-assisted learning using the Jigsaw method significantly enhanced comprehension, retention, communication skills, teamwork, confidence, and overall academic performance among MBBS Phase-I students. The method aligns well with CBME objectives and represents an effective student-centered teaching strategy in anatomy education.